Feasibility of Demolished Concrete and Scraped Tires in Peat Stabilization - A Review on the Sustainable approach in Stabilization - Ahmad, A. (Institute of Electrical and Electronics Engineers Inc., 2020)
The concrete waste originates from the demolition of concrete buildings, while tire waste generates by discarding a vehicle tire which is no longer safe to be used. Both wastes are collected in an enormous quantity in Malaysia and the amount is escalating yearly which is dumped legally or illegally in nearby sites, imposing serious environmental threats. On the other hand, peatland is widely spread across Malaysia which is considered the most undesirable construction foundation for any sort of infrastructure. It is associated with weak engineering properties such as low bearing capacity, high compressibility, and high water content, which need to be stabilized before the commencement of construction activities. Since both demolished concrete waste and shredded tire wastes have evidently enhanced the engineering characteristics of inorganic soil such as clay and sand. A comprehensive literature review of the online research work has carried out on the feasibility assessment of demolished concrete waste and shredded tire waste as a stabilizing agent in peat. Â© 2020 IEEE.